We cannot continue like this Facing modernity in Africa and Europe - van Niekerk, Attie (AOSIS, 2021)
The book is based on the view that the present trajectory of modern development cannot continue as it is now because it is ecologically unsustainable, it continues to enlarge the gap between rich and poor, and the decolonialisation movement has drawn our attention again to the specific role of religion, culture and value in human affairs and the need for a robust element of indigenisation and contextualisation. This book is strongly focused on the context of Africa, with two chapters that are written by authors from the Netherlands, for the purpose of presenting a North-South dialogue. The book contains reflection on approaches followed in building sustainable human communities in general and reflection on specific efforts to solve sustainability issues. It seeks to integrate academic reflection and insights gained from practical involvement with sustainability issues in local communities and low-income households, with contributions from Theology and Natural and Social Sciences.